2021
DOI: 10.1108/prt-03-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the process of dyeing cotton fabric with natural dyes from jackfruit wood by immersion without heating

Abstract: Purpose This paper aims to examine the recipe for and standard methods of dyeing cotton fabric with natural dyes from jackfruit wood extract. The dyeing of the fabric was performed by immersion it without heating for a short time to obtain the best results. Design/methodology/approach The dyeing experiment using cotton fabric with jackfruit wood extract was conducted by immersion at room temperature. The independent variables studied were the mordant method, type of mordant, mordant concentration, salt conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…In addition to phenolic compounds such as erulic acid, caffeic acid, and rutin in papaya fruit, lycopene, β-cryptoxanthin, and β-carotene were identified as carotenoids (Rivera‐Pastrana et al 2010 ). According to Rosyida et al ( 2022 ), cotton fabrics could be dyed with jackfruit wood extract, papaya fruit extract as a bio-mordant agent, and metallic mordants in one study. It has been reported that, depending on the mordant agents, green, purple, and gray color tones can be obtained with sufficient fastness properties.…”
Section: Mordant Agentsmentioning
confidence: 99%
“…In addition to phenolic compounds such as erulic acid, caffeic acid, and rutin in papaya fruit, lycopene, β-cryptoxanthin, and β-carotene were identified as carotenoids (Rivera‐Pastrana et al 2010 ). According to Rosyida et al ( 2022 ), cotton fabrics could be dyed with jackfruit wood extract, papaya fruit extract as a bio-mordant agent, and metallic mordants in one study. It has been reported that, depending on the mordant agents, green, purple, and gray color tones can be obtained with sufficient fastness properties.…”
Section: Mordant Agentsmentioning
confidence: 99%
“…Adanya kandungan mordan, yaitu logam aluminium pada serat/kain dalam jumlah yang lebih banyak menyebabkan penyerapan zat warna pada serat menjadi lebih cepat. Selain itu banyaknya kandungan mordan dalam serat juga menyebabkan serat dapat mengikat zat warna dengan jumlah lebih banyak sehingga hasil celupan diperoleh warna lebih tua [5]. Ini menyebabkan proses pencelupan menjadi lebih singkat.…”
Section: Apakah Proses Pewarnaan Zat Warna Alam Dapat Dilakukan Denga...unclassified